Eusociality outcompetes egalitarian and solitary strategies when resources are limited and reproduction is costly. Issue 24 (11th December 2018) - Fronhofer, Emanuel A.; Liebig, Jürgen; Mitesser, Oliver; Poethke, Hans Joachim
Abstract: Explaining the evolution and maintenance of animal groups remains a challenge. Surprisingly, fundamental ecological factors, such as resource variance and competition for limited resources, tend to be ignored in models of cooperation. We use a mathematical model previously developed to quantify the influence of different group sizes on resource use efficiency in egalitarian groups and extend its scope to groups with severe reproductive skew (eusocial groups). Accounting for resource limitation, the model allows calculation of optimal group sizes (highest resource use efficiency) and equilibrium population sizes in egalitarian as well as eusocial groups for a broad spectrum of environmental conditions (variance of resource supply). We show that, in contrast to egalitarian groups, eusocial groups may not only reduce variance in resource supply for survival, thus reducing the risk of starvation, they may also increase variance in resource supply for reproduction. The latter effect allows reproduction even in situations when resources are scarce. These two facets of eusocial groups, resource sharing for survival and resource pooling for reproduction, constitute two beneficial mechanisms of group formation. In a majority of environmental situations, these two benefits of eusociality increase resource use efficiency and lead to supersaturation—a strong increase in carrying capacity. The increase in resource use efficiency provides indirect benefits to group members even for low intra‐group relatedness and may represent one potential explanation for the evolution and especially the maintenance of eusociality and cooperative breeding. Abstract : Ecological factors, specifically resource variance and competition, tend to be ignored in models of social evolution. We here derive optimal resource sharing strategies, from egalitarian to eusocial groups. Our model shows that in most environmental conditions, eusociality trumps solitary and egalitarian living.